Analysis of Learning Styles of Students Majoring in Computer and Network Engineering - Nehemia Kristia; Krismiyati Krismiyati (International Journal of Active Learning, 2023)
This research was motivated by the ignorance of TKJ students at SMK Negeri 2 Salatiga about learning styles; some still need clarification about their learning styles. This research was conducted to analyze learning styles and know the dominant learning styles in grade X, XI, and XII TKJ SMK Negeri 2 Salatiga students. Also, to find out the most dominant learning style in TKJ students at SMK Negeri 2 Salatiga. The research method used quantitative descriptive with research subjects of 150 students selected using stratified random sampling techniques. Testing and data collection were done through Akupintar.id website and analyzed by frequency distribution. The results showed that class X TKJ 38% tended to have a kinesthetic visual mixed learning style, grade XI TKJ 56% tended to have a visual learning style, and XII TKJ 44% tended towards kinesthetic visual mixed learning style. Overall, students majoring in TKJ have the most dominant learning style, namely kinesthetic visual mixture, with a percentage of 82%. Students majoring in TKJ predominantly learn by involving their sense of sight and physique in the learning process. This research provides learning style analysis information for teachers as an evaluation material and future learning program plans.